Decriminalization of Blasphemy in National Criminal Law: A Theoretical Reflection - Darryl Evan Brouwer; Timothy Anggapermana Lande; Beatrice Briliany Immanuel (Faculty of Law, University of Dr. Soetomo, 2026)
Criminal law aims to suppress crime. As part of a social defense policy, crime suppression policy is directed at protecting the public. In this case, the authorities use criminal law as a social control instrument. However, this social control is limited by the human rights of individual citizens because the state must protect the human rights of individual citizens. Thus, the formulation of criminal law shall not be ambiguous and have multiple interpretations, thereby depriving citizens of their rights and freedom of religion. In the National Criminal Code, the crime of blasphemy has been decriminalized. This study analyzes whether the politics of decriminalization of the criminal act of blasphemy in the National Criminal Code from a legal theory and legal philosophy aspect is appropriate. As legal research, the normative methodology has been used in this article. This research concludes that the politics of decriminalization of the criminal act of blasphemy in the National Criminal Code and Penal Administration Law has its legitimation from the legal theoretical and legal philosophical aspects.